Study the Effect of Acetone and Ethyl Alcohol on the Curing Behavior and Mechanical Properties of Unsaturated Polyester Composites - منصور رامي; الحموي لطيفة; نعمان رؤيا (Latakia University Journal -Engineering Sciences Series, 2021)
The additives effect the behavior of unsaturated polyester curing curves, which forms the basis of understanding the behavior of formation process, regardless of their ratio. This research aims to study the effect of percentages (0,2,5,10%) of acetone and ethyl alcohol on the viscosity and behavior of the unsaturated polyester curing curves, in addition to the changes caused by these percentages in tension properties for the finished product of unsaturated polyester reinforced with a layer of jute. The results showed the similarity of curing curves behavior of the acetone and alcohol although the mechanism effect is different. The viscosity test shows that there is a low relative change in the values of the viscosity of UPR. By testing the samples on tensile strength, it was found that there was a decrease in the tensile stress values with the increase in percentage of Additives, as the tension decrease by (17.4 %) when adding (10%) acetone, while alcohol caused a decrease by (55.4%), it was also found that there was a slight improvement in the elongation at break, indicating that these materials played a plasticizer role for the UPR.